PERSEPSI KEMUDAHAN, CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN E-WALLET MELALUI - Desti Dirnaeni; Lies Handrijaningsih; Septi Mariani T.R; Anisah Anisah (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- The use of electronic money makes transactions practical, efficient and the recording of transactions is carried out automatically following the banking books. All these advantages become an attractiveness for people to use them in their daily transactions. This study aims to determine the effect of perception ease of use, customer relationship management and service quality on customer loyalty through customer satisfaction of DANA E-wallet users in Bekasi City. The population in this study were all active and passive users in using DANA, and the number of research samples was 100 respondents with path analysis as an analytical tool. The results showed that perceived convenience, customer relationship management and service quality had an effect on customer loyalty through customer satisfaction, either directly or indirectly. The most dominant variable on customer loyalty through customer satisfaction in this study is service quality. Keywords: Customer Loyalty; Customer Satisfaction; E-wallet